Privacy, reputation, and control: public figure privacy law in contemporary China. (3rd July 2021) - Dai, Xin
ABSTRACT: Privacy law, as it regulates the nonconsensual disclosure of personal life, is instrumental to how reputation in human society becomes created, destroyed, and redistributed. In the contemporary Chinese society, as in elsewhere, privacy protection, and the lack thereof, have played an important role in the making of the 'haves' and 'have-nots' in the society's reputation landscape. This Article makes a systematic effort towards accounting for China's contemporary legal regime that regulates its public figure privacy problems. Through examining leading court cases and relevant regulatory practices, this Article demonstrates that the Chinese privacy regime in the twenty-first century, as embedded in the country's overall information regulation apparatus, differs in significant ways from the corresponding Western paradigms in terms of its operational structure, cultural logic, and political dynamics. Since the beginning of the post-Cultural Revolution era, China's status-based privacy regime has for the most time been highly protective of government officials until they become expelled from the official ranks. It is often laissez-faire with respect to the privacy of famous individuals outside of the government system, but with notable exceptions for those enjoying an exalted status in the realm of high culture. Furthermore, it can be conspicuously hostile towards grassroot figures who aspire for the limelight. The impact such public figure privacy regime may have had on China's reputation landscape is conceivably regressive. As this Article explains, underlying such regime is a lasting, albeit evolving, cultural tradition that tends to associate privacy protection with a hierarchical moral outlook. Notwithstanding the importance of culture, this Article further argues that China's privacy regulation must also be understood as embedded in the country's political context. As the status-based privacy regime produces disparate reputational consequences, it provides the state with a lever to incentivize and manage a diverse network of elites, whom the state considers as agents for upholding its political and moral authority and implementing its policy agenda. China's privacy regime in the new millennium may thus be understood as having stemmed from an intricate political process as the state strategically responds to rising challenges from increasingly powerful and competing market and social forces over the production of information, fame, and influence.